Factors associated with poor neurological outcome in children after abusive head trauma: A multicenter retrospective study. (September 2022) - Regeffe, Fanny; Chevignard, Mathilde; Millet, Anne; Bellier, Alexandre; Wroblewski, Isabelle; Patural, Hugues; Javouhey, Etienne; Mortamet, Guillaume
Abstract: Background: Abusive Head Trauma (AHT) remains the leading cause of brain injury in infants. Objective: This study aims to describe a cohort of patients with AHT and identify early risk factors associated with poor neurological outcome. Participants and setting: Children under one year old admitted to a Pediatric Intensive Care Unit (PICU) with a suspected or confirmed diagnosis of AHT were included. Neurological outcome was assessed by the Pediatric Overall Performance Category score (POPC) at discharge from the hospital and at two years of follow-up. Methods: A multicentre retrospective study was conducted over 8 years (from January 2012 to December 2020). Results: A total of 117 patients (mean age 4.3 (+/− 2.5) months, 61 % boys) from three PICUs were included. A total of 99 (85 %) patients completed a 2-year follow-up. Sixty-one (52 %) and 47 (40 %) children with AHT had a POPC (pediatric overall performance category) score ≥ 2 at discharge from ICU and discharge from hospital, respectively (meaning they had at least a moderate disability). Fifty-one (44 %) had a POPC score ≥ 2 at 2-year follow-up, including 19 patients (19 %) with severe disabilities. The main neurological disabilities were neurodevelopmental ( n  = 38, 35 %), hyperactivity disorder ( n  = 36, 33 %) and epilepsy ( n  = 34, 31 %). After analysis according to the hierarchical model, the occurrence of a cardiorespiratory arrest and a low Glasgow Coma Score at admission stand out as factors of poor neurological outcome. Conclusion: This study highlights the wide range of neurological disabilities in children with AHT. Early and multidisciplinary follow-up is crucial to limit the impact of neurological disability.